Diagnostics and treatment of liver tuberculosis in a cancer patient - O. V. Velikaya; O. S. Martyshova; O. N. Chupis (Туберкулез и болезни лёгких)
The article describes a clinical case of diagnosis and successful treatment of liver tuberculosis in a 55-year-old female patient who has disability status (Group 1) due to cancer (acute myeloblastic leukaemia and mastectomy due to cancer in the past). Liver tuberculosis was diagnosed as a result of liver biopsy after focal changes had been detected by MSCT.